Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae). II. The species of the subgenera Pauciscleroblatta and Monoscleroblatta - Bohn, Horst (Zootaxa, 2020)
The present paper is a continuation of the revision of the genus Dziriblatta started with definition and description of the nine subgenera of the genus (Bohn 2019). In that first part of the revision usually only one species of each subgenus was described; the remaining species should be treated in following papers of which this contribution is the first dealing with the species of the subgenera Pauciscleroblatta (6 species) and Monoscleroblatta (4 species). Five species are new to science: Dziriblatta (Pauciscleroblatta) cyprica, spec. nov., Dz. (P.) habbachii, spec. nov., Dz. (P.) stenoptera, spec. nov., Dz. (P.) multiporosa, spec. nov., and Dz. (Monoscleroblatta) aglandulosa, spec. nov.                The descriptions are illustrated by numerous figures and determination keys allow the discrimination of the species. The geographical distribution of the species is shown on several maps. The species of Pauciscleroblatta are distributed in Algeria, Tunisia, Israel, West Bank, Syria (Golan) and Cyprus, those of Monoscleroblatta are restricted to northwestern Morocco.